Molecular and genetic characterization of allelic variants of microsatellite loci in parthenogenetic caucasian rock lizards Darevskia armeniaca (Lacertidae) - Malysheva, D. N.; Vergun, A. A.; Martirosyan, I. A.; Tokarskaya, O. N.; Ryskov, A. P. (Molecular genetics, microbiology and virology, 2008)
Using a pair of primers selected for the loci Du215, Du281, and Du323 of Darevskia unisexualis , monolocus PCR analysis of orthologous loci was carried out in populations of the related parthenogenetic species D. armeniaca and in populations of bisexual parental species D. valentini and D. mixta . It was shown that the studied loci were polymorphic and represented in populations of D. armeniaca by several allelic variants. We cloned and sequenced PCR amplification products of the allelic variants of Du215, Du281, and Du323 loci. It was found that allelic differences in microsatellite loci were caused by variations in the number of tandem repeats in the microsatellite clusters and point mutations in the flanking regions. An interspecies comparison of the orthologous locus Du215 between parthenogenetic species D. armeniaca and parental species showed that two allelic variants of Du215 in D. armeniaca were inherited from the parental bisexual species D. mixta and D. valentini . The third allelic variant was not found in parental species and appeared due to mutation processes in genome of parthenospecies. For the first time, the information about the molecular nature of allelic polymorphism of these microsatellite loci of parthenogenetic species D. armeniaca was received in this study.